Common application programming interface architecture bridge for connecting heterogeneous home computing middleware - Metwly, Nevin (University of Ottawa (Canada), 2010)
Microprocessors are now embedded in various equipments such as home appliances and digital audio/video devices, providing varieties of services. An integration of these services and creation of new ones is always needed to fulfill ongoing users' demands. There are a number of issues limiting the expandability of the intelligent home networks. One of these issues is that most middleware for home computing networks are not compatible with each other. To solve this problem of diversification of middleware and to ensure interoperability among them, the one-to-one bridge has been developed, which connects two specific middleware varieties and performs protocol conversion; also various one-to-any home network middleware bridges have lately been introduced. In this thesis, a proposal for any-to-any bridge connecting home computing middleware is introduced. It enables any appliance under any middleware to communicate and control any other appliances under different middleware. Also, new middleware can be easily integrated with the proposed architecture.
Keywords: Engineering, Electronics and Electrical.